Sex moderates the effects of experimentally induced musculoskeletal pain on alcohol demand in healthy drinkers. (1st February 2021) - Stennett, Bethany; Anderson, Molly B.; Vitus, Darya; Ferguson, Erin; Dallery, Jesse; Alappattu, Meryl; Robinson, Michael; Boissoneault, Jeff
Highlights: APT indices significantly correlate with self-report measures of drinking behavior. Delayed onset muscle soreness had sex-specific effects on alcohol demand. DOMS increased alcohol demand in men, but decreased demand in women. DOMS induction may be a useful model for characterizing pain-alcohol associations. Abstract: Background: Pain may serve as an antecedent for alcohol use, increasing risk for hazardous drinking and associated consequences. Delayed onset muscle soreness (DOMS) induction produces clinically relevant but time-limited musculoskeletal pain. This study was conducted to determine whether DOMS induction on the dominant elbow flexors influenced alcohol demand using the Alcohol Purchase Task (APT). We hypothesized DOMS would increase alcohol demand relative to a sham control. Based on existing studies of pain self-medication, we expected DOMS-related increases in alcohol demand would be greatest in men. Methods: Participants (N = 53; 57 % women) were randomly assigned to a DOMS (eccentric exercise) or sham condition (concentric exercise). Participants completed the APT pre-exercise and 48 -hs post-exercise. Repeated measures GLM was used to characterize group by sex by time interactions on APT indices, including intensity, breakpoint, essential value (EV), Omax, and Pmax . Results: The DOMS procedure significantly increased pain ratings at the elbow flexors. Men had significantly higher demand intensity than women across groups and time points. Significant interactive effects were detected for breakpoint and EV. From pre- to post-test, breakpoint significantly increased in men in the DOMS group. However, breakpoint and EV significantly decreased in women in the DOMS group. Conclusions: Increased alcohol demand in men in the DOMS group was consistent with epidemiological data suggesting men are at higher risk for self-medicating pain with alcohol than women. However, decreased demand in women was unexpected. Taken together, results indicate DOMS induction may be a useful means to characterize pain as an antecedent for alcohol use.